Interprofessional communication between community pharmacists and general practitioners: a qualitative study - Weißenborn, Marina; Haefeli, Walter E.; Peters-Klimm, Frank; Seidling, Hanna (International journal of clinical pharmacy, 2017)
Background While collaboration between community pharmacists (CPs) and general practitioners (GPs) is essential to provide comprehensive patient care, their communication often is scarce and hampered by multiple barriers. Objective We aimed to assess both professions’ perceptions of interprofessional communication with regard to content and methods of communication as a basis to subsequently develop best-practice recommendations for information exchange. Setting Ambulatory care setting in Germany. Method CPs and GPs shared their experience in focus groups and in-depth interviews which were conducted using a semi-structured interview guideline. Transcribed recordings were assessed using qualitative content analysis according to Mayring. Main outcome measure Specification of existing barriers, CPs’/GPs’ general perceptions of interprofessional communication and similarities and differences regarding prioritization of specific information items and how to best communicate with each other. Results Four focus groups and fourteen interviews were conducted. Seven internal (e.g. professions were not personally known to one another) and nine external barriers (e.g. mutual accessibility) were identified. Ten organizational, eight medication-related, and four patient-related information items were identified requiring interprofessional communication. Their relevance varied between the professions, e.g. CPs rated organizational issues higher than GPs. Both professions indicated communication via phone to be the most frequently used method of communication. Conclusion CPs and GPs opinions often differ. However, communication between CPs and GPs is perceived as crucial suggesting that a future concept has to offer standardized recommendations, while leaving CPs and GPs room to adjust it to their individual needs.
Gesehen am 22.11.2018